Interaksi Sosial antara Remaja Muslim dan Kristiani di Kelurahan Sei Sikambing B Medan - Syahbandi, Maulana; Harahap, Elly Warnisyah; Ekowati, Endang (ANWARUL, 2023)
Christians in the Village of Sei Sikambing B Medan. Adolescence is a period of transition from childhood to adulthood. Social interaction during adolescence is very important, because there are many developmental prerequisites that must be met during this period, namely physical development, psychological development, and especially social development. The method used in this study is a qualitative method with a phenomenological approach. The phenomenological approach is related to the understanding of everyday life and the intersubjective world (life world) of participants. Phenomenological research tries to explain or reveal the meaning of concepts or phenomena based on the awareness of experiences that occur in several individuals. In this research the instruments used are observation, interviews and documentation. Then the data were analyzed with qualitative research analysis. The results of the study show that the form of social interaction between Muslim and Christian adolescents leads to an associative process characterized by positive forms of social interaction that lead to a state of harmony and social unity.